Splitting test experimental dataset of hollow concrete blocks - José Álvarez-Pérez (Elsevier, 2021)
Masonry structures are widely used nowadays for their advantages like low-cost workmanship, efficiency and fast construction techniques. The compressive strength of the materials that compose masonry (block and mortar) is very important to the behavior of the system, but the tensile strength is even more significant for the standards and building codes. In this work, a dataset for indirect tensile tests of hollow concrete blocks is obtained. Splitting tests as described in ASTM C-1006-13 are applied. Two sets of blocks were tested, one with medium compressive strength and the other with high compressive strength. The first set was tested in three directions named A, B, and C; the second one was tested in two directions, A and B. The data was collected with a servo-hydraulic machine. The data is presented in tables and can be used by material researchers, as well as in numerical modeling.